Migrant welfare tactics and transnational social protection between Portugal and the UK - Machado, Bruno (2019)
Migration and the sustainability of the welfare state are irrefutably two essential topics in the political debate throughout Europe. Not only has the dominant pattern within the political discourse been focused on the generosity of benefits attracting migrants as, until recently, researchers tended to concentrate on the supposed “weight” of migration on destination countries. This view contrasts with new perspectives that highlight not only the levels of unawareness regarding benefits or social services in the destination countries as well as transnational practices involving a myriad of formal and informal providers across borders. Drawing on qualitative data gathered through 39 interviews conducted with British migrants in Portugal and Portuguese migrants in the UK, we explore migrants’ welfare experiences. Deploying the idea of social protection assemblages, which is the combination of formal and informal elements of protection, the analysis explores the welfare tactics that migrants adopt across transnational space to ensure their social welfare needs are met in the present and future. Local social capital, social networks and the process of welfare learning are key aspects in navigating the welfare system in the destination. Simultaneously, transnational practices are employed to overcome the gaps in formal services, either by piecing two formal social protection systems or informal elements provided by interpersonal networks. We demonstrate the importance of happenstance and “just in case” practices as well as cultural values and other non-economic factors as bearing a deep impact on how migrants ‘do’ social protection. .